Mathematical Model Transmission Dynamics of Onychomycosis with Cymbopogon Citratus Application as Control on Patients in Selected Hospitals in Benue State, Nigeria - Magdalene, Tyona Ngodoo (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
Onychomycosis, a fungal nail infection, presents significant public health challenges, including in Benue State, Nigeria. Traditional plants like Cymbopogon citratus (lemon grass) have demonstrated antifungal properties. This study develops a mathematical model to analyze onychomycosis transmission dynamics and evaluate C. citratus extracts as a potential treatment. The model uses ordinary differential equations, categorizing individuals as susceptible (S), infected (I), and recovered (R) over time. Simulations show that reducing contact with infected individuals lowers transmission rates. Consistent treatment with C. citratus increases recovery, thereby decreasing susceptibility. Numerical simulations reveal that applying C. citratus extracts using a sterilized nail polish brush over two years resulted in reduced infection. The treatment regimen involved bi-weekly application for up to two years, with periodic monitoring of nail improvement. The study highlights that isolating infected individuals, combined with treatment and environmental precautions (such as avoiding shared nail equipment and walking barefoot in contaminated areas), significantly reduces transmission. These findings suggest that early detection, isolation, and consistent treatment with C. citratus are key to managing and potentially eradicating onychomycosis in the population.